PENGARUH MOTIF DAN INTENSITAS PENGGUNAAN MEDIA ONLINE MANGAKU.WEB.ID TERHADAP KEPUASAN HIMPUNAN MANGAKA PEKANBARU - Baffi, Muhammad Raevanoe; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The popularity of online media in society, especially among teenagers, is based on the motive. The motive in using online media can lead to an intensity in using online media that will affect satisfaction in using online media. Mangaku.web.id. is one of the popular web manga among Japanese culture lovers. In the theory of uses and gratification, to meet the needs, society choose its own media based on motive and the media only provide what is needed by the community. The purpose of this research is to know how big influence between motif and intensity of media usage to satisfaction of Himpunan Mangaka Pekanbaru. The method used in this research is quantitative explanative. The data were collected using questionnaires. The research was conducted at Himpunan Mangaka Pekanbaru. The sample in this study amounted to 96 respondents. The sampling technique uses accidental sampling. The analysis test used in this research is path analysis and to process the questionnaire data, done by using program SPSS for Windows version 23. The results obtained from path analysis in this study is the motive of online media use has a direct influence on online media usage satisfaction of 15.9% and indirect influence on online media use satisfaction through the intensity of online media usage of 1.1%. Thus the total effect obtained in this study is 17%, while the rest is influenced by other factors that are not in this study. Keywords: Motive, Intensity, Satisfaction, Manga, Media Usage